The patient paradigm shifts : profiling the new healthcare consumer - Chan, Judy L. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
The dynamics of healthcare are shifting the patient paradigm in dramatic ways. The former patient is now both a consumer and a customer. The mantra of this new consumer is "convenient, fast, simple, and high value." Their expectations for healthcare are similar to what they experience in other industries such as transportation, banking, short-stay rental housing, retail shopping online, same-day deliveries, and more. Smart mobile devices enable the customer to conduct transactions at any place and at any time, and without waiting in line. Healthcare providers need to offer customer service experiences similar to Apple, Amazon, Nordstrom, and other benchmark companies in order to stay competitive. The mindset of the new patient-turned-consumer has fundamentally shifted and there is no looking back. Anyone connected to healthcare needs to learn the profiles of the new consumer, better understand their behaviors, and comprehend their expectations as customers who have a choice. The patient paradigm shifts tells you everything a successful business needs to know about the powerful new healthcare consumer.
1. Transformation of healthcare: it's about time and money -- 2. Healthcare joins the 21st century: moving from paper to binary -- 3. We pay and pay for healthcare -- 4. Reframing healthcare delivery: my time and my place -- 5. Consumers are us -- 6. Communication gets a facelift -- 7. In transparency do we trust? -- 8. Right time, right place: improving quality at the point of treatment -- 9. The new old: aging dynamically -- 10. Converging data for better healthcare -- 11. Thoughts on the future -- Appendix: additional resources -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on March 3, 2017).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Patient-centered health care -- United States; Medical care -- United States; Medical technology -- Social aspects -- United States; Patient-Centered Care; Delivery of Health Care; Biomedical Technology; United States; Affordable Care Act (ACA); big data; consumer; consumerism; consumer profile; cost of health care; customer; EHR adoption; health; healthcare; health information exchange; health insurance; healthcare transformation; interoperability; ObamaCare; patient; patient-turned-consumer; precision medicine; transparency; Electronic books